Views of key stakeholders on deprescribing preventive medication in people living with dementia: a qualitative systematic review protocol - Nikolaos Efstathiou; Ian Maidment; Clare Bates; Claire Sutton; Nesrein Hamed (BMJ Open)
Introduction As people get older, they tend to take more preventive medication such as statins, beta-blockers and anti-coagulants to help prolong their lives. The risks of taking medication can start to outweigh the benefits in older people, and whether those with comorbidities want to extend these years of poor health is another consideration. One-third of older people will develop dementia, and they may not have the mental capacity to decide whether to continue or withdraw preventive medication. In these cases, deprescribing is left to advocates, such as healthcare professionals and family members. This systematic review will look at the views of stakeholders, including advocates, people living with dementia and any other people involved in the decision-making process for deprescribing preventive medication in dementia.Methods and analysis A systematic review of qualitative evidence using thematic synthesis and an inductive approach will be conducted. The following databases and platforms will be searched: Embase, HMIC, MEDLINE, PsycINFO, CINAHL, PubMed, Cochrane Central Library, OATD, ProQuest, Scopus and the Web of Science, along with manual searches through citation mining and grey literature. Only primary qualitative studies (or the qualitative elements of mixed method studies) will be used. There will be no date limit, and the search will be completed by April 2025. Only English-language articles will be used. The included studies will present views and experiences about deprescribing specifically preventive medication in dementia cases. Principles identified by Cochrane for qualitative studies will be used as guidance. Covidence will facilitate two independent reviewers to identify relevant studies, and the Critical Appraisal Skills Programme and Mixed Methods Appraisal Tool will be used to assess quality. NVivo will be used to manage the extracted findings from the included studies.Ethics and dissemination Ethical approval is not applicable for this study as no original data is going to be collected as it is a systematic review. The findings will be disseminated in a peer-reviewed open-access publication and at conference presentations.PROSPERO registration number CRD42023476394. Any changes made to the protocol will be reported on PROSPERO.